Radar and Communication Co-Existence Design Based on Mutual Information Optimization - Qian, Junhui; Lu, Mengchen; Huang, Nuo (IEEE transactions on circuits and systems. II, Express briefs, 2020)
In this brief, we proposed and analyzed a novel algorithmic framework for radar and communication co-existence design based on mutual information (MI) optimization. The objects of interest in design are the radar transmit code, receive filter, and the communication system code-book, whereby we state the design problem as a constrained maximization of the communication MI subject to a number of constraints guaranteeing both the communication and radar performance, through a similarity constraint with some standard waveform and the effective power of radar interference under the power limited conditions. The proposed approach is based on iterative alternating optimization of three suitably designed subproblems, whose solutions are derived and analyzed in closed form, and the convergence is analytically proved. Finally, we assess the effectiveness of the proposed approaches by numerical results.